House prices and superstition among ethnic Chinese and non-Chinese homebuyers in Auckland, New Zealand. Issue 1 (27th November 2017) - Rehm, Michael; Chen, Shuzhen; Filippova, Olga
Abstract : Purpose: Numerical superstition is well-known in Asian countries and can influence decision-making in many markets, from financial investment to purchasing a house. This study aims to determine the house price effects of superstition and understand if these have changed over time. Design/methodology/approach: Using sales transactions of freestanding houses in Auckland, New Zealand, the authors use hedonic price analysis to investigate whether superstitious beliefs associated with lucky and unlucky house numbers affect property values. Findings: The analysis reveals ethnic Chinese buyers in Auckland displayed superstitious home buying behaviour in the period 2003-2006 by attributing value to homes with street addresses starting or ending with the lucky number eight. However, this willing to pay higher prices for lucky numbers was not reflected in the analysis of 2011-2015 sales transactions. The disappearance of superstition price effects may indicate that ethnic Chinese in the Auckland housing market have, over time, assimilated New Zealand's Western culture and have become less superstitious. Originality/value: Unlike previous studies, the authors parse buyers into two populations of homebuyers, ethnic Chinese and non-Chinese purchasers, and model the two groups' housing transactions independently to more accurately establish if numerical superstition influences house prices.